Differential analyses of leaf proteomes in oil palm seedlings inoculated with pathogenic and nonpathogenic species of ganoderma - Rahmad, Norasfaliza (2017)
Basal stem rot (BSR) is a destructive disease of oil palm caused by the basiodiomycete fungus known as Ganoderma spp. Basal stem rot disease is considered the most serious disease affecting commercial oil palm plantations in South East Asia, especially in Malaysia and Indonesia. The disease reduces the productivity and yield of infected oil palm by disrupting water and nutrient movement from the roots to the other parts of the plant. Until now, there is no protein biomarker available to detect BSR disease at early stage of infection due to the insufficient information of Ganoderma spp. and most of the analyses related to the interaction between oil palm and Ganoderma spp. were conducted using roots tissues which require destructive sampling. Therefore, the objective of this study is to search for specific responsive protein candidates for early and non-destructive protein-based disease detection method by using leaf sample. Proteomic analysis of oil palm leaf was conducted on samples collected 72 hours following introduction of oil palm seedlings onto the mycelium of G. boninense and G.tornatum in flask. It is hypothesized that specific responsive proteins related to defence mechanism will be differently expressed by the leaf protein from oil palm seedling inoculated with G. boninese compared to the uninoculated control and G.tornatum-inoculated seedlings. A total of 82 proteins were resolved by two-dimensional gel electrophoresis with significant differences in the spot abundance. From there, 24 differentially expressed proteins in response to Ganoderma spp. inoculations were successfully identified by mass spectrophotometry (MALDI TOF/TOF). The proteins are mainly involved in photosynthesis and energy metabolism, RNA and protein metabolism as well as stress/defence mechanism. Proteins related to photosynthesis and energy production such as ATP synthase and ribulose bisphosphate carboxylase (Rubisco) were downregulated while proteins such as 70kDa heat shock protein and cyclophilin which involves in protein metabolism were up-regulated in comparison to un-inoculated sample. Defence related proteins, WAK proteins was up-regulated while hyrdroxyproline-rich glycoprotein like protein (HRGP) and mannose-binding lectin were down-regulated during the mycelium attachment process. Based on predicted cellular function classification, this study managed to identify several specific responsive proteins that can be used as possible candidates for biomarker or biological indicator for BSR early detection in oil palm which is important to properly manage the disease.